Study on the Surface Water Allocation for Domestic, Agricultural and Hydropower for Myogyi Dam in Myanmar - Thida Mon, Wint; May Ei Nandar Soe (AI Society & STMIK Indonesia, 2025)
This study presents surface water allocation for domestic, agricultural, and hydropower sectors in the Kyaukse District of Myanmar, focusing on the Myogyi Dam as the primary water source. Myogyi Dam is constructed across the flow of Zawgyi river and divided into four canals such as Ngabyaung Canal, Thindwe Canal, Minye Canal and Zeedaw Canal. As domestic water distribution network, Zawgyi river is connected to Kyaukse township. Utilizing the CROPWAT 8.0 and WEAP models, the research analyzes water demand, unmet demand, and site coverage from the year 2024 to the year 2054. Crop water requirements are estimated using long-term meteorological data and local crop parameters and WEAP simulations evaluate allocation efficiency across interconnected demand sites. According to the results of reference scenarios, the domestic supply zone and most irrigated areas are able to meet their respective water demands. However, the Ngabyaung irrigated area face a significant shortfall, requiring an additional 6900 million gallons to fulfill its demand. While all other areas achieve full demand site coverage, Ngabyaung lag behind with only 25% coverage. The total unmet demand of hydropower is approximately 35,000 megawatt-hours, and the demand site coverage remains at 100% throughout the year, except during the months of November and December.